China's elite politics : political transition and power balancing - Bo, Zhiyue (Hackensack, N.J. : World Scientific, 2007)
China?s Elite Politics provides a new theoretical perspective on elite politics in China and uses this theoretical perspective to explain power transfer from Jiang Zemin to Hu Jintao and political dynamics between different factional groups since the Sixteenth Party Congress of November 2002. It explains the transition in structural terms, presents characteristics of China?s political elites, and analyzes the balance of power among formal institutions as well as among factional groups. It also examines political interactions between Jiang Zemin and his cronies on the one side and Hu Jintao and.
List of Tables and Figures; Acknowledgments; Introduction: Toward a Power Balancing Model on Elite Politics in China; WINNER-TAKES-ALL MODEL; BANDWAGON POLITICS MODEL; BALANCE-OF-POWER POLITICS MODEL; POWER BALANCING MODEL; POWER BALANCING MODEL AND ITS COMPETING MODELS; CHAPTER OUTLINE; Part I: Political Transition and Power Balance; 1. Power Transfer from Jiang Zemin to Hu Jintao at the Sixteenth Party Congress; 2. The Sixteenth Central Committee: Technocrats in Command?; 3. Balance of Formal Power; 4. Balance of Factional Power; Part II: Dynamics of Factional Politics.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Elite (Social sciences) -- China; Balance of power; China -- Politics and government -- 1949-; Élite (Sciences sociales) -- Chine; Équilibre des puissances; Chine -- Politique et gouvernement -- 1949-; POLITICAL SCIENCE -- Political Process -- General; Balance of power; Elite (Social sciences); Politics and government; China; Since 1949